The fate of glycerol entering the rumen of dairy cows and sheep. Issue 2 (24th September 2014) - Werner Omazic, A.; Kronqvist, C.; Zhongyan, L.; Martens, H.; Holtenius, K.
Summary This study investigated the fate of glycerol entering the rumen, in particular whether glycerol could be absorbed across the rumen epithelium. Three non‐lactating rumen‐fistulated cows were used to calculate the overall disappearance rate of glycerol in vivo and evaluate the rate of ruminal glycerol absorption. Rumen epithelial tissues isolated from sheep were used to characterise glycerol transport properties. The rate of rumen microbial degradation of glycerol was then studied in an in vitro system under anaerobic and thermo‐regulated conditions. The results showed that glycerol can be absorbed from the rumen in significant amounts. The fractional rate of absorption of glycerol was not affected by variations in glycerol concentration in the buffer solution in the in vivo study. The glycerol absorption apparently occurred largely by passive diffusion and was probably not facilitated by carriers. Glycerol also disappeared via microbial digestion and outflow from the rumen through the omasal orifice.